(untitled) (Literary Voice, 2024)
Code-switching and its pros and cons, is a highly debated phenomenon in second language learning in a classroom setting. This study also discusses how hindering code-switching affects the learning process in English language classrooms. The data for this quantitative study was gathered from the population of 50 BS second language learners at the University of Lahore through a 5-point Likert scale questionnaire. The results indicate that the majority of undergraduate learners have a favorable disposition towards the practice of code-switching. They face difficulties when they are not allowed to switch codes in the classroom. However, it has been found that there are a few learners who do not feel any difficulty in the absence of code-switching opportunities. According to the findings, stopping the learners from code-switching in educational settings is disadvantageous. The encouragement of code-switching practice in classrooms is a robust way of enhancing communicative skills, socio-emotional engagement, and accelerating learning outcomes. These findings have important implications for language educators and policymakers and will help in fulfilling the actual classroom requirements and bringing about a change in the attitudes towards code-switching.